RANCANG BANGUN MESIN PELET BIOMASSA TERINTEGRASI DENGAN PENDEKATAN DIAGRAM FAST - Gusti Hardiansyah; Ivan Sujana; Ratih Rahmahwati; M. Taufiqurrahman (Fakultas Kehutanan Universitas Mulawarman, 2020)
The purpose of this research is to support and encourage the development of sustainable palm oil, reduce the environmental impact caused by the rehabilitation of oil palm plants that are not well managed by the managers of oil palm plantations and produce technological.Therefore, in-depth analysis is needed related to the innovation of biomass pellet printing machine (biopellet) technology using the diagram function Function Analysis and System Technique (FAST). Analysis is done by determining the critical functions that must be present in an integrated biomass pellet machine (biopellet) on the performance of a machine that can produce biomass pellets (biopellet) and is moveable. The results of the study using the FAST approach produce engine design that has the main function in a biopellet machine that is moveable by considering the critical functions such as the cutting function of waste palm stalks, enumeration functions, raw material mixing functions, pellet printing functions and skeleton holder functions that can integrate all functions engine by considering the moveable nature of the engine. It is hoped that this research can be developed even better starting from the quality of the cutting edge of the blade on the machine and the printing quality of the biopellet.